Verb-form errors in EAP writing - Wee, Roselind; Sim, Jacqueline; Jusoff, Kamaruzaman (Academic Journals, 2010)
This study was conducted to identify and describe the written verb-form errors found in the EAP writing of 39 second year learners pursuing a three-year Diploma Programme from a public university in Malaysia. Data for this study, which were collected from a written 350-word discursive essay, were analyzed to determine the types and frequency of verb form errors. The subjects’ verb-form errors were identified and categorized under four category types: omission, addition, misformation and ordering. The findings revealed that the subjects made the most number of errors in the omission verb-forms in the area of the third person singular verb (-s/-es/-ies). This occurred when they tried to make the verb agree with the singular subject or plural subject by dropping the -s inflection from the third person singular verb or making the verb plural by adding the –s inflection, respectively. The frequencies of errors of addition and misformation were almost the same while verb-form errors of ordering had the least number of errors. The copula ‘’be’’ verb was a major problematic area. The subjects tended to over-generalize and, hence, either omitted the ‘’be’’ verb or used it wrongly. Errors in writing will affect the readability and quality of the piece of work. So, in this light, the subjects’ verb-form errors have to be identified so that they can be equipped with the basics of producing error-free writing.